INNOVATIVE DESIGN TO IMPROVE THE PERFORMANCE OF AIR FILTERS THROUGH THE USE OF ULTRASONIC TRANSDUCERS AND HIGH ION THRUSTER - H. M. Gadjiyev; S. M. Magomedov; T. A. Chelushkina; A. S. Shkurko (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The article considers the possibility to increase the efficiency of the air filter by applying a high-voltage ion propulsion and the ultrasonic transducers.